Frequency and Perinatal outcome in patients with tight Nuchal Cord - Shazia Zulfiqar , Madiha Khalid , Sidra Naeem , Shazia Zulfiqar , Madiha Khalid , Sidra Naeem (Journal of Rawalpindi Medical College, 2019)
Background: The nuchal cord is often blamed for problems that are encountered during delivery and is often cited as a major cause of fetal distress and perinatal mortality. However, the actual significance of nuchal cord on the outcome of an infant is controversial. Objective: To determine the frequency of tight nuchal cord in patients with fetal distress and to determine the perinatal outcome in patients with nuchal cord. Material & Methods: Study Design: Descriptive cross sectional Setting: Department of Obstetrics & Gynaecology Fatima Memorial Hospital, Lahore Duration: Six months i.e. From: September 2014___ to May 2015 Results: In our study, out of 350 cases, 62%(n=217) were between 18-30 years of age and 38%(n=133) were between 31-35 years. the mean age was 27.86±4.60 years, frequency of patients having tight nuchal cord, in patients with fetal distress presenting in a tertiary care hospital was calculated as 32%(n=112). Frequency of perinatal outcome in patients having tight nuchal cord was recorded which shows that 34 (30.36%) had emergency cesarean section, 39 (34.82%) had APGAR score <7 at 1 min and 9 (8.04%) had APGAR score at 5 mins. Conclusion: We concluded that the frequency of patients having tight nuchal cord, in patients with fetal distress presenting in a tertiary care hospital is higher while emergency cesarean section and APGAR score <7 at 1 minute are the most common adverse perinatal outcome among these patients.